ART OF THE EURASIAN STEPPE its influence on european cultures. - Hupfauf, Peter ([S.l.] : ROUTLEDGE, 2024)
The Art of the Eurasian Steppe is a contextual analysis which traces the stylistic transformation of artefacts depicting animals from various cultures of the Eurasian steppe, and investigates its possible influence on Central and Northern European art. A wide range of individual cultures are "visited" and their historic, cultural, and geographic specifics are explored. The survey in this book is based on a chronological structure, including an East-West geographic direction. This accommodates to position described artefacts of certain styles within time periods, cultures, and locations. Most of the existing literature related to cultures of the Eurasian steppe is specialised on one particular culture or one archaeological excavation. The book is written as a hypothetical journey through time and space, structured in an east to west direction. It provides a wide-reaching overview by placing the discussed artefacts into a cultural, geographic, and chronologic frame, particularly the thousand years between 500 BC and 500 AD. Artistic expression and style are a central theme to explore possible relationships between civilisations of the Eurasian steppe and their influence on medieval Central and Northern European creation of artefacts. Academics in the fields of art history, archaeology, history, and fine arts will find this book compelling/useful.
Keywords: Art -- Eurasia; ART / History / General